2019
DOI: 10.3747/co.26.4679
|View full text |Cite
|
Sign up to set email alerts
|

Dignity and Its Influencing Factors in Patients with Cancer in North China: A Cross-Sectional Study

Abstract: Background Patients with cancer experience various levels of loss of dignity. Exploring levels of loss of dignity and the factors that influence such losses for patients with cancer is rare, but important in palliative care in China.Methods Participants were cancer patients with early and advanced cancer recruited from a tertiary cancer hospital in North China. Patients were surveyed to assess their level of loss of dignity and potentially relevant factors. Data were collected using the Patient Dignity Invento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 14 publications
1
45
1
3
Order By: Relevance
“…Psychosocial status includes the patients' level of psychological distress, as well as communication, closeness and social support. Patients with a higher level of depression and anxiety, 39,41,43,44 or with poor communication, 32 or detrimental interactions with the closed others 38 had a higher level of dignity‐related distress. Social support was positively associated with patients' sense of dignity 36,41 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychosocial status includes the patients' level of psychological distress, as well as communication, closeness and social support. Patients with a higher level of depression and anxiety, 39,41,43,44 or with poor communication, 32 or detrimental interactions with the closed others 38 had a higher level of dignity‐related distress. Social support was positively associated with patients' sense of dignity 36,41 …”
Section: Resultsmentioning
confidence: 99%
“…Wang et al 41 Mainland China 1 A cross-sectional study (n = 202). Measurements were PDI, MDASI-C, NCCN-DT, HADS and EQLQ-30.…”
Section: Perception Of Dignitymentioning
confidence: 99%
“…Os problemas com dignidade eram ligeiramente diferentes em pacientes com doença em estágio inicial do que naqueles com doença em estágio avançado. A idade, a ansiedade e a carga de sintomas foram preditores significativos de perda de dignidade (Wang et al, 2019).…”
Section: Metodologiaunclassified
“…Studies of dignity and end‐of‐life care have shown that there is a strong association between an undermining of dignity and desire for death, depression, anxiety, hopelessness, feeling of being a burden on families and poorer quality of life (HM et al, ; HM, ). Importantly, advanced cancer patients deem a sense of dignity and spiritual peace, relieving burden and strengthening relationships with loved ones as some important facets of palliative care (Ho et al, ; Wang, Wei, Xue, Guo, & Liu, ). A systematic review showed that spiritual care including dignity therapy had a potentially beneficial effect on the quality of life and spiritual well‐being of patients with terminal illness, suggesting that healthcare professionals should pay greater attention to patients’ spiritual well‐being (Chen, Lin, Yan, Wu, & Hu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of dignity and end-of-life care have shown that there is a strong association between an undermining of dignity and desire for death, depression, anxiety, hopelessness, feeling of being a burden on families and poorer quality of life (HM et al, 2002;HM, 2002). Importantly, advanced cancer patients deem a sense of dignity and spiritual peace, relieving burden and strengthening relationships with loved ones as some important facets of palliative care (Ho et al, 2013;Wang, Wei, Xue, Guo, & Liu, 2019).…”
mentioning
confidence: 99%